2020
DOI: 10.1002/lno.11549
|View full text |Cite
|
Sign up to set email alerts
|

Reproducing the virus‐to‐copepod link in Arctic mesocosms using host fitness optimization

Abstract: By shunting material out of the predatory pathway toward detritus and dissolved material, viruses are believed to have an important impact on biogeochemical functions of the pelagic microbial food web. To include viruses as a single plankton functional type (PFT) in dynamic food web models is, however, not trivial since they will then compete with predators for the same host/prey community as a shared limiting resource. As recently shown, one can solve this problem by introducing adaptation in the defensive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…For example, DOM from Phaeocystis blooms may be very abundant but of inferior quality for bacteria due to low nitrogen content (Olli et al, 2019). Thus, variability in top-down (predation) and bottom-up (availability and quality of DOM and inorganic nutrients) control leads to bacterial communities with different competition and defense properties and may affect the overall carbon and nutrient flow in the system (Sandaa et al, 2017;Tsagaraki et al, 2018;Thingstad et al, 2020).…”
Section: Microbesmentioning
confidence: 99%
“…For example, DOM from Phaeocystis blooms may be very abundant but of inferior quality for bacteria due to low nitrogen content (Olli et al, 2019). Thus, variability in top-down (predation) and bottom-up (availability and quality of DOM and inorganic nutrients) control leads to bacterial communities with different competition and defense properties and may affect the overall carbon and nutrient flow in the system (Sandaa et al, 2017;Tsagaraki et al, 2018;Thingstad et al, 2020).…”
Section: Microbesmentioning
confidence: 99%
“…Thingstad et al [102] summarized the impact of viruses on the pelagic microbial food web, particularly in Arctic mesocosms, and the challenge of incorporating viruses into dynamic food web models. Viruses are recognized for redirecting material away from the predatory pathway toward detritus and dissolved material, influencing biogeochemical functions.…”
Section: Copepod-virus Interactionsmentioning
confidence: 99%
“…It has also been proposed that viruses can be significant drivers of the BP, via their facilitation of particle aggregation and transfer to the deep sea, leading to their dual “shunt and pump” roles (Suttle 2007; Lomas and Moran 2011). The relationships between the BP and MCP and of the viral shunt and pump in biogeochemical cycling is, nevertheless, yet to be determined, as diverse groups of eukaryotic viruses have been documented in the ocean, with different lineages functioning differently (Blanc‐Mathieu et al 2019), due to their host‐strain specificity (Breitbart 2012; Thingstad et al 2021).…”
Section: From Loops and Shunts To Pumpsmentioning
confidence: 99%
“…Even for those species that are not directly toxic, mixoplanktonic activity and allelopathy may be synergistic: the mixoplankton gain while the competitors affected by allelopathic compounds do not (e.g., John et al 2015). All of these interactions lay themselves open to interference from virus attack, and all of them will affect, in one way or the other, the functioning of the microbial loop and therefore the MCP (Flynn et al 2021; Thingstad et al 2021). Further, mixoplanktonic activity alters the stability of a plankton community, and models have suggested that open ocean plankton dynamics may have a more stable equilibrium and higher production rates due to enhanced nutrient feedbacks (e.g., Mitra et al 2014; Leles et al 2021).…”
Section: Implications Of the Mixoplankton Paradigm For The Food‐web A...mentioning
confidence: 99%